Foundations of intelligent systems : 12th International Symposium, ISMIS 2000 Charlotte, NC, USA, October 11-14, 2000, Proceedings - Ras, Zbigniew; Osuga, Setsuo, 1934- (Lecture notes in computer science. Lecture notes in artificial intelligence., 2010)
This book constitutes the refereed proceedings of the 12th International Symposium on Methodologies for Intelligent Systems, ISMIS 2000, held in Charlotte, NC, USA in October 2000. The 64 revised full papers presented together with one invited contribution were carefully reviewed and selected from a total of 112 submissions. The papers are organized in topical sections on evolutionary computation, intelligent information retrieval, intelligent information systems, knowledge representation and integration, knowledge discovery and learning, logic for AI, and methodologies.